KDELR1 Is an Independent Prognostic Predictor and Correlates With Immunity in Glioma - Yuan, Yifan; Yang, Biao; Qi, Zengxin; Han, Zhenyuan; Cai, Jiajun; Song, Jianping (Frontiers in Oncology, 2022)
Background: Gliomas are the most malignant central nervous system tumors. With the development of sequencing technology, more potential biomarkers related to the treatment, prognosis and molecular classification of glioma have been identified. Here, we intend to investigate the potential biological function and clinical value of a new biomarker in glioma. Methods: KDELR1 expression data and corresponding clinical information were downloaded from public databases and then preprocessed using R language. Correlation, Kaplan–Meier survival and Cox regression analyses were performed to explore the clinical significance of KDELR1 in glioma patients. Furthermore, the immune infiltration and microenvironment parameters were evaluated via TIMER and CIBERSORT. Immunohistochemistry was conducted to confirm the KDELR1 expression and its correlation with immunity infiltration and prognosis. Results: KDELR1 was upregulated in glioma samples compared with normal brain tissues, and its expression was significantly correlated with age, WHO grade, recurrence, necrosis, microvascular proliferation, molecular classification, IDH mutation and 1p/19q codeletion status. In addition, survival analysis showed that glioma patients with KDELR1 overexpression had shorter overall survival and disease-free survival times, and Cox regression analysis revealed that KDELR1 acted as an independent prognostic factor of OS (overall survival) in glioma patients. GSEA (Gene Set Enrichment Analysis) indicated significant enrichment of metabolism-associated pathways. KDELR1 expression was positively associated with immune infiltration (including infiltration by CD8+ T cells, CD4+ T cells, macrophages and so on) and microenvironment parameters (including stromal, immune and ESTIMATE scores) in gliomas. The expression of KDELR1 and its correlation with tumor grade and prognosis were confirmed by immunohistochemistry in clinical samples (n = 119, P < 0.05). Conclusions: Taken together, these findings suggest that KDELR1 is correlated with tumor grade, molecular classifications and immune infiltration; highlighting that KDELR1 is a novel and promising biomarker for molecular classification, treatment and prognostic assessment, may furtherly indicating the treating effect of immune therapy.